Estimating measles transmission potential in Italy over the period 2010-2011 - Marco Ajelli; Stefano Merler; Laura Fumanelli; Antonino Bella; Caterina Rizzo (Istituto Superiore di Sanità, 2014)
BACKGROUND: Recent history of measles epidemiology in Italy is characterized by the recurrence of spatially localized epidemics. AIM: In this study we investigate the three major outbreaks occurred in Italy over the period 2010-2011 and estimate the measles transmission potential. The epidemics mainly involved individuals aged 10-28 years and the transmission potential, measured as effective reproduction number - i.e. the number of new infections generated by a primary infector - was estimated to be 1.9-5.9. RESULTS: Despite such high values, we found that, in all investigated outbreaks, the reproduction number has remained above the epidemic threshold for no more than twelve weeks, suggesting that measles may hardly have the potential to give rise to new nationwide epidemics. CONCLUSION: In conclusion, the performed analysis highlights the need of planning additional vaccination programs targeting those age classes currently showing a higher susceptibility to infection, in order not to compromise the elimination goal by 2015.